Brucellosis in sub-Saharan Africa: Epidemiology, control and impact - McDermott, John J.; Arimi, S.M. (Elsevier, 2002)
Brucellosis is an important disease among livestock and people in sub-Saharan Africa. In general, the incidence is the highest in pastoral production systems and decreases as herd size and size of landholding decreases. The prevalence of risk factors for infections are best understood for bovine brucellosis and to a lesser extent for ovine and caprine brucellosis. The occurrence and epidemiology of brucellosis in pigs is poorly understood. This species bias is also reflected in control activities. As with other public-sector animal health services, the surveillance and control of brucellosis in sub-Saharan Africa is rarely implemented outside southern Africa. Brucellosis is even more ignored in humans and most cases go undiagnosed and untreated, leading to considerable suffering for those affected. Decision-making to determine the importance of brucellosis control relative to other public concerns and what brucellosis control strategies should be applied is urgently required. A strategy for how brucellosis decision-making might be considered and applied in future is outlined.